Profilowanie psychologiczne seryjnych zabójców - Gawenda, Adriana (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The interest in the phenomenon of serial killing, became the subject of many disputes. Scientists, on the basis of performed tests, tried to present theories explaining why a will appears in a man to deprive another man of his life. Many of them distinguished, as a basis, an acute feeling of aggression associated with every human being, which gives it free rein in the form of an act of murder. Within the interest, there was not only an attempt to characterize the psychological profile of the perpetrators of multiple murders, but also victimology. This article is mainly intended to gather knowledge on serial killers, but also to formulate new theses trying to explain the phenomenon of serial killings.This is a representation of both scientific theories to explain the presence of serial killers, as well as coverage of the typology of such criminals. In this paper, some comparisons are also drawn between the manner conduct of different types of serial killers. The article also contains the essential elements on the basis of which a psychological portrait of the perpetrator of killing is formed.
Keywords: seryjny morderca; typologia zabójców; profilowanie psychologiczne; metody dedukcyjne